ETNOMATEMATIKA DAN PELESTARIAN BUDAYA BATIK: SEBUAH STUDI KUALITATIF-ETNOGRAFIS TENTANG KONSEP MATEMATIKA DALAM BATIK CEPLOK KASATRIAN - Santosa, Yoga Tegar; Maulida, Dini Wardani; Irmanopaliza, Ade; Ishartono, Naufal (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2025)
Batik Ceplok Kasatrian is an Indonesian cultural heritage that is full of philosophical meaning but is less known by the younger generation. Therefore, the integration of batik in mathematics learning can be one of the strategies to preserve tradition of batik culture. This research aims to explore mathematical concepts, such as geometry, algebra, arithmetic, and statistics, in Batik Ceplok Kasatrian motifs. This research uses qualitative-ethnographic. The subject of this study is the Batik Ceplok Kasatrian motif. Data validity is obtained through source triangulation, while data analysis includes reduction, presentation, and conclusion. The exploration process is carried out by answering four main questions: